330 Socioeconomic Factors, Perioperative Complications, and 30-Day Readmission Rates Associated With Delayed Referral for Cranial Vault Reconstruction for Craniosynostosis. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Sergesketter, Amanda; Elsamadicy, Aladine A; Kemeny, Hanna; Harward, Stephen C; Krucoff, Kate B; Krucoff, Max O; Fuchs, Herbert E; Thompson, Eric M; Allori, Alexander; Marcus, Jeffrey; Muh, Carrie R
Abstract: INTRODUCTION: Craniosynostosis is the premature fusion of cranial sutures that may lead to neurocognitive, developmental, and aesthetic consequences. As such, a timely intervention with cranial vault reconstruction (CVR) is necessary to optimize patient outcomes. However, there is a paucity of data regarding the impact that delayed surgical correction has on perioperative complications and 30-d readmission rates. The aim of this study was to identify the drivers of delayed CVR and its impact on perioperative complication and 30-d readmission rates. METHODS: The medical records of 135 children who underwent primary CVR for craniosynostosis between 2005 and 2017 at a single academic institution were retrospectively reviewed. A delay in operation was defined by primary surgery performed >12 mo of age. Patients who underwent intentional delayed CVR due to medical comorbidities were excluded. Patient demographics, comorbidities, perioperative complication rates, length of hospital stay, and 30-d readmission rates were collected. RESULTS: A total of 96 patients who underwent primary CVR met the inclusion criteria of this study, with 79 (82.3%) patients undergoing a nondelayed surgery versus 17 (17.7%) patients undergoing a delayed surgery at >12 mo of age. The mean ± standard deviation (SD) age at surgery was significantly higher among the delayed cohort (no delay: 244.8 ± 54.5 d vs delay: 759.2 ± 409.0 d, P  < .0001). Children undergoing delayed surgery were significantly more likely to be non-White ( P  < .0001), have Medicaid insurance ( P  = .023), and have a non-English primary language ( P  < .005). There was increased incidence of preoperative developmental disability identified at first consult (no delay: 3.9% vs delay: 41.2%, P  < .0001) and preoperative increased intracranial pressure (no delay: 6.3% vs delay: 29.4%, P  < .005) among children undergoing delayed surgery. There were no significant differences in intra- and postoperative complication rates; however, the delayed cohort had a significantly higher unplanned 30-d readmission rate (no delay: 0.0% vs delay: 5.9%, P  = .03). CONCLUSION: Our study suggests that craniosynostosis patients who are non-White, have a non-English primary language, and have Medicaid insurance are at risk for delayed primary surgery. In turn, delayed primary CVR was associated with higher 30-d readmission rates. Further studies are necessary to better understand how to reduce delays to primary CVR in these populations.